Positive electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
By using a lithium transition metal composite oxide positive electrode active material with a higher Ti molar fraction on smaller particles, the challenges of resistance increase and capacity decrease in nonaqueous electrolyte secondary batteries are addressed, resulting in improved battery performance.
Patent Information
- Application Number
- JP2021537681
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-05
- Filing Date
- 2020-07-21
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-07-21
AI Technical Summary
Nonaqueous electrolyte secondary batteries, such as lithium-ion batteries, face challenges in suppressing the increase in resistance and decrease in capacity due to charge and discharge, particularly with positive electrode active materials having high energy density.
The positive electrode active material consists of lithium transition metal composite oxide with 80 mol% or more Ni content, where Ti is present on the surface of the particles. By using particles with larger and smaller sizes, the molar fraction of Ti on the surface of smaller particles is higher than on larger particles, which helps in suppressing the increase in resistance and decrease in capacity.
This approach effectively suppresses the increase in resistance and decrease in capacity associated with charging and discharging, enhancing the performance and longevity of nonaqueous electrolyte secondary batteries.
Smart Images

Figure 0007662523000003 
Figure 0007662523000001 
Figure 0007662523000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a positive electrode active material for a non-aqueous electrolyte secondary battery, and a non-aqueous electrolyte secondary battery using the positive electrode active material. [Background technology]
[0002] In recent years, lithium transition metal composite oxides with a high Ni content have been attracting attention as positive electrode active materials with high energy density. For example, Patent Document 1 discloses a surface-modified lithium nickel composite oxide obtained by making a compound (such as titanium oxide) of an element of Groups 4B to 6B of the periodic table, the element having an oxide melting point of 750°C or higher, present on the particle surface of a composite oxide with a high Ni content, and then calcining the composite oxide. Patent Document 1 describes that the high-temperature storage stability of the battery, particularly the impedance change, can be dramatically improved. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2004-253305 A Summary of the Invention
[0004] In non-aqueous electrolyte secondary batteries such as lithium ion batteries, it is important to suppress the increase in resistance and the decrease in capacity that accompanies charging and discharging. The technology disclosed in Patent Document 1 still has room for improvement in terms of suppressing both the increase in resistance and the decrease in capacity.
[0005] An object of the present disclosure is to suppress an increase in resistance and a decrease in capacity that occur during charging and discharging in a non-aqueous electrolyte secondary battery that includes a positive electrode active material with a high energy density.
[0006] The positive electrode active material for a non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure contains 80 mol % or more of Ni relative to the total number of moles of metal elements excluding Li. Also contains Co and MnThe positive electrode active material contains a lithium transition metal composite oxide having a volumetric particle diameter larger than a 70% particle diameter (D70) and a volumetric particle diameter smaller than a 30% particle diameter (D30), and when the first particle is a particle having a volumetric particle diameter smaller than a 30% particle diameter (D30), Ti is present at least on the particle surface of the second particle. T Mole fraction of i (A2) is a surface of the first particle T Mole fraction of i (A1) It is characterized in that it is larger than
[0007] A non-aqueous electrolyte secondary battery according to one embodiment of the present disclosure includes a positive electrode containing the above positive electrode active material, a negative electrode, and a non-aqueous electrolyte.
[0008] According to the positive electrode active material of one embodiment of the present disclosure, it is possible to provide a nonaqueous electrolyte secondary battery in which an increase in resistance and a decrease in capacity due to charging and discharging are suppressed. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery according to an embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present inventors have conducted extensive research to solve the above problems, and have found that the increase in resistance and the decrease in capacity associated with charging and discharging are specifically suppressed by increasing the molar fraction of Ti on the surface of the second particles having a small particle size compared to the molar fraction of Ti on the surface of the first particles having a large particle size. In small particles such as the second particles, metals constituting the composite oxide are more likely to dissolve during charging and discharging than in large particles such as the first particles. It is presumed that the dissolution of such metals is one of the causes of the increase in resistance and the decrease in capacity associated with charging and discharging. It is believed that the presence of a large amount of Ti on the surface of the small particles suppresses the dissolution of the metals, thereby achieving the above effects. Note that Ti is mainly present in the form of lithium titanate on the particle surface of the lithium transition metal composite oxide.
[0011] Hereinafter, an example of an embodiment of the positive electrode active material for nonaqueous electrolyte secondary batteries according to the present disclosure and a nonaqueous electrolyte secondary battery using the positive electrode active material will be described in detail. Hereinafter, a cylindrical battery in which a wound electrode body 14 is housed in a cylindrical outer can 16 with a bottom will be exemplified, but the outer can is not limited to a cylindrical outer can, and may be, for example, a rectangular outer can, or may be an outer can made of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body may be a laminated type electrode body in which multiple positive electrodes and multiple negative electrodes are alternately stacked with separators interposed therebetween.
[0012] FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 according to an embodiment. As illustrated in FIG. 1, the nonaqueous electrolyte secondary battery 10 includes a wound electrode assembly 14, a nonaqueous electrolyte, and an exterior can 16 that accommodates the electrode assembly 14 and the electrolyte. The electrode assembly 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The exterior can 16 is a cylindrical metal container with a bottom that is open on one axial side, and the opening of the exterior can 16 is closed by a sealing body 17. In the following description, for convenience of explanation, the sealing body 17 side of the battery is referred to as the top, and the bottom side of the exterior can 16 is referred to as the bottom.
[0013] The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. For example, esters, ethers, nitriles, amides, and mixed solvents of two or more of these are used as the non-aqueous solvent. The non-aqueous solvent may contain a halogen-substituted product in which at least a part of the hydrogen of these solvents is replaced with a halogen atom such as fluorine. For the electrolyte salt, for example, a lithium salt such as LiPF6 is used. The electrolyte is not limited to a liquid electrolyte, and may be a solid electrolyte using a gel-like polymer or the like.
[0014] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all long strip-shaped bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound in a spiral shape. The negative electrode 12 is formed to be slightly larger than the positive electrode 11 in order to prevent lithium deposition. That is, the negative electrode 12 is formed to be longer than the positive electrode 11 in the longitudinal direction and the width direction (short direction). The two separators 13 are formed to be at least slightly larger than the positive electrode 11, and are arranged to sandwich the positive electrode 11, for example. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0015] Insulating plates 18 and 19 are disposed above and below the electrode body 14. In the example shown in Fig. 1, the positive electrode lead 20 passes through a through hole in the insulating plate 18 and extends toward the sealing body 17, and the negative electrode lead 21 passes outside the insulating plate 19 and extends toward the bottom side of the outer casing 16. The positive electrode lead 20 is connected to the lower surface of an internal terminal plate 23 of the sealing body 17 by welding or the like, and a cap 27, which is a top plate of the sealing body 17 and is electrically connected to the internal terminal plate 23, serves as a positive electrode terminal. The negative electrode lead 21 is connected to the inner bottom inner surface of the outer casing 16 by welding or the like, and the outer casing 16 serves as a negative electrode terminal.
[0016] A gasket 28 is provided between the exterior can 16 and the sealing body 17 to ensure airtightness inside the battery. The exterior can 16 has a grooved portion 22 formed therein, with part of the side surface protruding inward, to support the sealing body 17. The grooved portion 22 is preferably formed in an annular shape along the circumferential direction of the exterior can 16, and supports the sealing body 17 on its upper surface. The sealing body 17 is fixed to the top of the exterior can 16 by the grooved portion 22 and the open end of the exterior can 16 which is crimped against the sealing body 17.
[0017] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26, and a cap 27 are laminated in this order from the electrode body 14 side. Each member constituting the sealing body 17 has, for example, a disk shape or a ring shape, and each member except the insulating member 25 is electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective centers, and the insulating member 25 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, the lower valve body 24 deforms and breaks so as to push the upper valve body 26 toward the cap 27, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure further increases, the upper valve body 26 breaks, and gas is discharged from the opening of the cap 27.
[0018] The positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14, and in particular the positive electrode active material that constitutes the positive electrode 11, will be described in detail below.
[0019] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode composite layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film with the metal disposed on the surface layer, or the like can be used. The positive electrode composite layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core except for the part to which the positive electrode lead 20 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode composite slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode composite layer on both sides of the positive electrode core.
[0020] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).
[0021] The positive electrode active material includes particles of a lithium transition metal composite oxide containing 80 mol % or more of Ni with respect to the total number of moles of metal elements excluding Li. By making the Ni content 80 mol % or more, a battery with a high energy density can be obtained. In addition, in the lithium transition metal composite oxide, Ti is present at least on the particle surface. Hereinafter, for convenience of explanation, the lithium transition metal composite oxide is referred to as "composite oxide (Z)". The positive electrode active material may be composed essentially of the composite oxide (Z) alone, with the composite oxide (Z) as the main component. The positive electrode active material may contain a composite oxide other than the composite oxide (Z) or other compounds within a range that does not impair the object of the present disclosure.
[0022] The composite oxide (Z) may contain a metal element other than Li, Ni, and Ti. Examples of the metal element include Co, Mn, Al, Zr, B, Mg, Fe, Cu, Zn, Sn, Na, K, Ba, Sr, Ca, W, Mo, Nb, and Si. An example of a suitable composite oxide (Z) is represented by the general formula Li a Ni b Co c Mn d Ti e O f (wherein, 0.8≦a≦1.2, b≧0.82, c≦0.12, 0.03≦d≦0.12, 0.01≦e≦0.05, 1≦f≦2). That is, the molar fraction of Ti (proportion of the number of moles of Ti) relative to the total number of moles of metal elements excluding Li is preferably 0.01 to 0.05.
[0023] The composite oxide (Z) is, for example, a secondary particle formed by agglomeration of a plurality of primary particles. The particle size of the primary particles constituting the secondary particles is, for example, 0.05 μm to 1 μm. The particle size of the primary particles is measured as the diameter of a circumscribed circle in a particle image observed by a scanning electron microscope (SEM). Ti is present on the surface of the secondary particles of the composite oxide (Z) as well as on the surface of the primary particles. In addition, a part of Ti is also present inside the primary particles, and may form a solid solution with other metal elements contained in the composite oxide (Z).
[0024] The composite oxide (Z) is a particle having a volume-based median diameter (D50) of, for example, 3 μm to 30 μm, preferably 5 μm to 25 μm, and particularly preferably 7 μm to 15 μm. D50 means a particle diameter at which the cumulative frequency is 50% from the smallest particle diameter in the volume-based particle size distribution, and is also called the median diameter. The particle size distribution of the composite oxide (Z) can be measured using a laser diffraction type particle size distribution measuring device (e.g., MT3000II manufactured by Microtrack Bell Co., Ltd.) with water as a dispersion medium.
[0025] The composite oxide (Z) is characterized in that, when particles having a volumetric particle size larger than 70% particle size (D70) are defined as first particles and particles having a volumetric particle size smaller than 30% particle size (D30) are defined as second particles, the molar fraction of Ti on the surface of the second particles is higher than the molar fraction of Ti on the surface of the first particles. The second particles may include particles having a molar fraction of Ti on the surface that is the same as or lower than the molar fraction of Ti on the surface of the first particles.
[0026] Here, D70 means a particle size where the cumulative frequency is 70% from the smallest particle size in the volumetric particle size distribution. Similarly, D30 means a particle size where the cumulative frequency is 30% from the smallest particle size in the volumetric particle size distribution. For example, D70 is 9 μm to 19 μm, and D30 is 3 μm to 13 μm. The molar fraction of metal elements present on the particle surface of the complex oxide (Z) is measured by X-ray photoelectron spectroscopy (XPS). The molar fraction of metal elements in the entire particle of the complex oxide (Z) is measured by inductively coupled plasma (ICP) emission spectroscopy.
[0027] In the composite oxide (Z), the molar fraction (A2) of Ti with respect to the total molar amount of metal elements on the surface of the second particles is larger than the molar fraction (A1) of Ti with respect to the total molar amount of metal elements on the surface of the first particles. By controlling the amount of Ti on the particle surface so that A1 < A2, it is possible to suppress the increase in resistance and the decrease in capacity accompanying charge and discharge. The molar fraction (A1) is determined, for example, by XPS for the first particles. The irradiation spot diameter of the X-ray is preferably 0.03 mmΦ or more, more preferably 0.1 mmΦ or more, and particularly preferably 1 mmΦ or more, and it is preferable that several to several hundred first particles are included in the spot (the same applies to the molar fraction (A2)). In XPS, generally, elements present from 2 nm to 8 nm from the outermost surface of the particles are the measurement targets.
[0028] On the particle surface of the composite oxide (Z), Ti is mainly Li x Ti y O z exists in the state of lithium titanate represented by. In the formula, x, y, and z are, for example, 1 ≤ x ≤ 4, 1 ≤ y ≤ 5, and 1 ≤ z ≤ 12. As described later, as the Ti source, Ti compounds such as titanium oxide (TiO2) are used, but they react with Li present on the particle surface during firing to form Li x Ti y O z is generated.
[0029] Lithium titanate may be formed so as to cover the entire surface of the secondary particles, or may be scattered on the particle surface. In the case of particles, the particle size of lithium titanate is generally smaller than the particle size of the primary particles constituting the composite oxide (Z). Incidentally, the particles of lithium titanate can be confirmed by SEM. It is preferable that lithium titanate is attached over a wide range without being unevenly distributed on a part of the surface of the primary particles constituting the composite oxide (Z).
[0030] The ratio (A2 / A1) of the molar fraction (A2) of Ti on the surface of the second particle to the molar fraction (A1) of Ti on the surface of the first particle is preferably 1.10 or more, more preferably 1.15 or more, and particularly preferably 1.20 or more. In particular, when A2 / A1≧1.20, the increase in resistance and the decrease in capacity due to charging and discharging can be more highly suppressed. The upper limit of A2 / A1 is not particularly limited.
[0031] As described above, in the composite oxide (Z), Ti is present inside the primary particles and may be dissolved in a solid solution with transition metal elements such as Ni. The molar fraction of Ti relative to the dissolved metal elements can be confirmed by energy dispersive X-ray spectroscopy (EDS) in the cross section of the primary particles. In the composite oxide (Z), the total molar number of Ti in the lithium titanate present in the solid solution state and on the surface is preferably 0.01 to 0.05 relative to the total molar number of metal elements excluding Li.
[0032] In addition, in the composite oxide (Z), the ratio of the molar fraction of Ti present on the particle surface to the molar fraction of Ti in the whole particle (molar fraction of Ti on the particle surface / molar fraction of Ti in the whole particle) is preferably larger in the second particle than in the first particle. That is, the second particle contains many particles in which this ratio is larger than that of the first particle. In this case, the increase in resistance and the decrease in capacity due to charging and discharging can be suppressed to a higher degree.
[0033] The composite oxide (Z) can be prepared, for example, by the following procedure. (1) A Li source such as lithium hydroxide is added to two types of composite compounds that do not contain Li or Ti and have different D50, and the compounds are fired to synthesize lithium composite oxides (Z1) and (Z2) that have different D50. An example of the composite compound is a composite oxide or hydroxide that contains Ni, Co, and Mn. At this time, one type of lithium composite oxide may be classified to obtain lithium composite oxides having two types of average particle sizes. A conventionally known method can be used for the classification. (2) Add a Ti source to each of the composite oxides (Z1) and (Z2), complex Ti on the particle surface, then bake, and then mix the composite oxides (Z1) and (Z2). An example of the Ti source is titanium oxide (TiO2). For complexing, a dry particle complexing device (for example, NOB-130 manufactured by Hosokawa Micron Corporation) etc. is used. At this time, a Li source such as lithium hydroxide may be added together with the Ti source.
[0034] The baking temperature in the above step (2) is, for example, 550°C to 750°C. The lower the temperature, the larger the amount of lithium titanate generated on the surface of the primary particles, and the tendency for the solid solution amount of Ti to decrease. By making the addition amount of Ti to the small particles larger than the addition amount of Ti to the large particles, a state of A1 < A2 can be obtained. Also, by making the baking temperature of the small particles lower than the baking temperature of the large particles, a state of A1 < A2 can also be obtained.
[0035] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode composite layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal stable within the potential range of the negative electrode 12 such as copper, a film with the metal disposed on the surface layer, etc. can be used. The negative electrode composite layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core excluding, for example, the portion to which the negative electrode lead 21 is connected. The negative electrode 12 can be manufactured, for example, by applying a negative electrode composite slurry containing a negative electrode active material and a binder etc. on the surface of the negative electrode core, drying the coating film, and then compressing to form the negative electrode composite layer on both sides of the negative electrode core.
[0036] The negative electrode composite layer contains, as the negative electrode active material, for example, a carbon-based active material that reversibly occludes and releases lithium ions. Suitable carbon-based active materials are graphite such as flake graphite, massive graphite, and earthy graphite, artificial graphite such as massive artificial graphite (MAG), and mesophase carbon microbeads (MCMB) etc. Also, as the negative electrode active material, a Si-based active material composed of at least one of Si and Si-containing compounds may be used, or a carbon-based active material and a Si-based active material may be used in combination.
[0037] The binder contained in the negative electrode mixture layer may be, as in the case of the positive electrode 11, a fluororesin, PAN, polyimide, acrylic resin, polyolefin, or the like, but it is preferable to use styrene-butadiene rubber (SBR). The negative electrode mixture layer preferably further contains CMC or a salt thereof, polyacrylic acid (PAA) or a salt thereof, polyvinyl alcohol (PVA), or the like. Among them, it is preferable to use SBR in combination with CMC or a salt thereof, or PAA or a salt thereof.
[0038] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous thin film, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably a polyolefin such as polyethylene or polypropylene, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer or the like may be formed on the surface of the separator. EXAMPLES
[0039] The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0040] <Example 1> [Synthesis of positive electrode active material] Obtained by coprecipitation, D50 is 14μm and the composition is Ni 0.84 Co 0.10 Mn 0.06 (OH)2 nickel cobalt manganese composite hydroxide and D50 of 10μm and composition of Ni 0.84 Co 0.10 Mn 0.06 The nickel-cobalt-manganese composite hydroxides of (OH)2 were each calcined at 500°C to obtain a nickel-cobalt-manganese composite oxide (X1) having a large average particle size and a nickel-cobalt-manganese composite oxide (Y1) having a small average particle size.
[0041] Next, lithium hydroxide and a nickel-cobalt-manganese composite oxide (X1) having a large average particle size were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08: 1. This mixture was fired at 700°C in an oxygen atmosphere for 8 hours and then pulverized to obtain a lithium composite oxide (X2) having a large average particle size.
[0042] Next, lithium hydroxide and nickel-cobalt-manganese composite oxide (Y1) having a small average particle size were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn was 1.08: 1. This mixture was fired at 700°C in an oxygen atmosphere for 8 hours and then pulverized to obtain lithium composite oxide (Y2) having a small average particle size.
[0043] Next, the lithium composite oxide (X2) with a large average particle size and titanium oxide (TiO2) were dry mixed so that the molar ratio of the total amount of Ni, Co, and Mn to Ti in TiO2 was 1:0.02, and Ti was composited onto the particle surface. This mixture was fired at 700°C for 8 hours in an oxygen atmosphere and then pulverized to obtain a lithium composite oxide (X3) with Ti present on the particle surface.
[0044] Next, the lithium composite oxide (Y2) with a small average particle size was dry-mixed with TiO2 so that the molar ratio of the total amount of Ni, Co, and Mn to Ti in TiO2 was 1:0.025, and Ti was composited on the particle surface. This mixture was fired at 700°C for 8 hours in an oxygen atmosphere and then pulverized to obtain a lithium composite oxide (Y3) with Ti present on the particle surface.
[0045] Next, the lithium composite oxides (X3) and (Y3) were mixed in a 1:1 mass ratio to prepare the positive electrode active material. The amount of Ti present on the particle surface can be quantified by XPS, and the amount of Ti in solid solution can be quantified by EDS. The presence of Ti on the particle surface in the form of lithium titanium oxide can be confirmed by XRD, XPS, XAFS, etc.
[0046] The ratio (A2 / A1) of the molar fraction (A2) of Ti on the surface of the second particle having a volumetric particle size smaller than D30 to the molar fraction (A1) of Ti on the surface of the first particle having a volumetric particle size larger than D70 was 1.17. The molar fraction of Ti in each particle was determined by XPS.
[0047] In addition, the composition of the positive electrode active material was analyzed by ICP, and the results showed that Li 1.01 Ni 0.81 Co 0.10 Mn 0.06 Ti 0.02 The particle size distribution of the positive electrode active material was D50 of 12 μm, D70 of 14 μm, and D30 of 10 μm.
[0048] [Preparation of positive electrode] The positive electrode active material, acetylene black, and polyvinylidene fluoride (PVdF) were mixed in a solid content mass ratio of 96.3:2.5:1.2, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added, followed by kneading to prepare a positive electrode composite slurry. The positive electrode composite slurry was applied to both sides of a positive electrode core made of aluminum foil, and the coating was dried. The coating was then rolled using a roller and cut to a predetermined electrode size to obtain a positive electrode in which a positive electrode composite layer was formed on both sides of the positive electrode core. An exposed portion was provided in part of the positive electrode, exposing the surface of the positive electrode core.
[0049] [Preparation of negative electrode] Natural graphite was used as the negative electrode active material. The negative electrode active material, sodium carboxymethylcellulose (CMC-Na), and styrene-butadiene rubber (SBR) were mixed in an aqueous solution at a solid content mass ratio of 100:1:1 to prepare a negative electrode composite slurry. The negative electrode composite slurry was applied to both sides of a negative electrode core made of copper foil, and the coating film was dried. The coating film was then rolled using a roller and cut to a predetermined electrode size to obtain a negative electrode in which a negative electrode composite layer was formed on both sides of the negative electrode core. An exposed portion was provided in part of the negative electrode, where the surface of the negative electrode core was exposed.
[0050] [Preparation of non-aqueous electrolyte] Lithium hexafluorophosphate (LiPF6) was dissolved at a concentration of 1.0 mol / L in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 3:3:4. Furthermore, vinylene carbonate (VC) was dissolved at a concentration of 2.0 mass% in the mixed solvent to prepare a nonaqueous electrolyte.
[0051] [Battery construction] An aluminum lead was attached to the exposed part of the positive electrode, and a nickel lead was attached to the exposed part of the negative electrode, and the positive and negative electrodes were spirally wound with a polyolefin separator interposed therebetween, and then pressed in the radial direction to produce a flat wound electrode body. This electrode body was housed in an exterior body made of an aluminum laminate sheet, and the nonaqueous electrolyte was injected, and the opening of the exterior body was sealed to obtain a nonaqueous electrolyte secondary battery with a design capacity of 650 mAh.
[0052] <Example 2> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the synthesis of the positive electrode active material, a lithium composite oxide (Y2) having a small average particle size and TiO2 were mixed so that the molar ratio of the total amount of Ni, Co, and Mn to Ti in TiO2 was 1:0.03.
[0053] <Example 3> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that the firing conditions for the lithium composite oxide (Y3) having a small average particle size and having Ti composited on the particle surface were changed to 600° C. and 8 hours.
[0054] <Example 4> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the synthesis of the positive electrode active material, lithium hydroxide, a nickel-cobalt-manganese composite oxide (X1) having a large average particle size, and titanium oxide (TiO2) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn, and the molar ratio of Ti in TiO2 were 1.08:1:0.01.
[0055] <Example 5> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the synthesis of the positive electrode active material, lithium hydroxide, a nickel-cobalt-manganese composite oxide (Y1) having a small average particle size, and titanium oxide (TiO2) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn, and the molar ratio of Ti in TiO2 were 1.08:1:0.01.
[0056] <Example 6> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the synthesis of the positive electrode active material, lithium hydroxide, a nickel-cobalt-manganese composite oxide (X1) having a large average particle size, and titanium oxide (TiO2) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn, and the molar ratio of Ti in TiO2 were 1.08:1:0.01, and lithium hydroxide, a nickel-cobalt-manganese composite oxide (Y1) having a small average particle size, and titanium oxide (TiO2) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn, and the molar ratio of Ti in TiO2 were 1.08:1:0.01.
[0057] <Comparative Example 1> A non-aqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that in the synthesis of the positive electrode active material, the mixing of TiO2 and the subsequent firing were not carried out.
[0058] <Comparative Example 2> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 1, except that in the synthesis of the positive electrode active material, a mixture obtained by mixing a lithium composite oxide (X2) having a large average particle size and a lithium composite oxide (Y2) having a small average particle size in a mass ratio of 1:1 and TiO2 were dry-mixed such that the molar ratio of the total amount of Ni, Co, and Mn to Ti in TiO2 was 1:0.02.
[0059] <Comparative Example 3> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 6, except that in the synthesis of the positive electrode active material, the lithium composite oxide (X2) having a large average particle size and titanium oxide (TiO2) were not mixed and then fired, and the lithium composite oxide (Y2) having a small average particle size and TiO2 were not mixed and then fired.
[0060] <Comparative Example 4> A nonaqueous electrolyte secondary battery was produced in the same manner as in Example 5, except that in the synthesis of the positive electrode active material, the lithium composite oxide (X2) having a large average particle size and titanium oxide (TiO2) were not mixed and then fired, and the lithium composite oxide (Y2) having a small average particle size and TiO2 were not mixed and then fired.
[0061] <Comparative Example 5> In the synthesis of the positive electrode active material, lithium hydroxide, a nickel-cobalt-manganese composite oxide (Y1) having a small average particle size, and titanium oxide (TiO2) were mixed so that the molar ratio of Li to the total amount of Ni, Co, and Mn and the molar ratio of Ti in TiO2 were 1.08:1:0.015, and a nonaqueous electrolyte secondary battery was produced in the same manner as in Example 6 except that the lithium composite oxide (X2) having a large average particle size and titanium oxide (TiO2) were not mixed and then fired, and the lithium composite oxide (Y2) having a small average particle size and TiO2 were not mixed and then fired.
[0062] <Comparative Example 6> A non-aqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that molybdenum oxide (MoO3) was used instead of TiO2 in the synthesis of the positive electrode active material.
[0063] <Comparative Example 7> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 2, except that MoO3 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0064] <Comparative Example 8> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 3, except that MoO3 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0065] <Comparative Example 9> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 4, except that MoO3 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0066] <Comparative Example 10> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 5, except that MoO3 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0067] <Comparative Example 11> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 6, except that MoO3 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0068] <Comparative Example 12> A non-aqueous electrolyte secondary battery was fabricated in the same manner as in Example 1, except that tantalum oxide (Ta2O5) was used instead of TiO2 in the synthesis of the positive electrode active material.
[0069] <Comparative Example 13> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 2, except that in the synthesis of the positive electrode active material, Ta2O5 was used instead of TiO2.
[0070] <Comparative Example 14> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 3, except that Ta2O5 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0071] <Comparative Example 15> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 4, except that Ta2O5 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0072] <Comparative Example 16> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 5, except that Ta2O5 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0073] <Comparative Example 17> A nonaqueous electrolyte secondary battery was fabricated in the same manner as in Example 6, except that Ta2O5 was used instead of TiO2 in the synthesis of the positive electrode active material.
[0074] A cycle test was carried out for each battery of the examples and comparative examples, and the resistance increase rate and capacity retention rate were evaluated. The evaluation results are shown in Tables 1 and 2. Furthermore, Tables 1 and 2 show the metal element (Me) added to the nickel-cobalt-manganese composite oxide, the ratio (A2 / A1) of the molar fraction (A2) of Me on the surface of the second particle to the molar fraction (A1) of Me on the surface of the first particle, and the ratio of the molar fraction of Ti present on the particle surface to the molar fraction of Ti in the entire particle (LiMe O These figures show which of the first and second particles has a larger Me content (amount of Me in the first particle / amount of Me in the entire particle).
[0075] [Evaluation of resistance increase rate after cycle test] Each battery of the examples and comparative examples was charged to half of its initial capacity at a constant current of 0.5 It in a temperature environment of 25°C, and then the charging was stopped and left for 15 minutes. Then, the battery was charged for 10 seconds at a constant current of 0.1 It, and the voltage was measured. After discharging the charge capacity for 10 seconds, the current value was changed and the battery was charged for 10 seconds, the voltage at that time was measured, and then the charge capacity for 10 seconds was discharged. The charge / discharge and voltage measurement were repeated at current values from 0.1 It to 2 It. The resistance value was calculated from the relationship between the measured voltage value and current value, and was used as the resistance value before the cycle test.
[0076] The following cycle test was carried out, and the resistance value after 150 cycles was obtained by the above method, and the resistance increase rate was calculated by the following formula. The resistance increase rates shown in Tables 1 and 2 are relative values when the resistance increase rate of the battery of Example 1 is set to 100.
[0077] Resistance increase rate (%) = (resistance value after 150 cycles ÷ resistance value before cycle test) × 100 <Cycle test> The test cell was charged at a constant current of 0.5 It in a temperature environment of 60°C until the battery voltage reached 4.2 V, and then charged at a constant voltage until the current value reached 1 / 50 It at 4.2 V. Then, the test cell was discharged at a constant current of 0.5 It until the battery voltage reached 2.5 V. This charge / discharge cycle was repeated 150 times.
[0078] [Evaluation of capacity retention rate after cycle testing] For each battery of the Examples and Comparative Examples, the discharge capacity at the first cycle and the discharge capacity at the 150th cycle of the cycle test were determined, and the capacity retention rate was calculated by the following formula.
[0079] Capacity retention rate (%) = (150th cycle discharge capacity ÷ 1st cycle discharge capacity) × 100
[0080] [Table 1]
[0081] [Table 2]
[0082] As shown in Tables 1 and 2, the batteries of the Examples all had a significantly lower resistance increase rate and a significantly higher capacity retention rate than the batteries of the Comparative Examples. In other words, it can be seen that the resistance increase and capacity decrease accompanying charge and discharge are highly suppressed in the batteries of the Examples. In addition, particularly excellent effects were obtained when A2 / A1 was 1.20 or more (Examples 2 and 3) and when the LiMeO amount / Me amount in the entire particle was first particle<second particle (Example 3).
[0083] When A2 / A1 was 1.00 or less as in the comparative battery, and when elements other than Ti (Mo, Ta) were added to the nickel-cobalt-manganese composite oxide even when A2 / A1 exceeded 1.00, the resistance increased significantly during charging and discharging, and the capacity decreased significantly. Even when Ti was added, when it was dissolved inside the primary particles, not on the surface, the resistance increased significantly during charging and discharging, and the capacity decreased significantly. [Explanation of symbols]
[0084] 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 16 Outer can 17 Sealing body 18,19 Insulating plate 20 Positive lead 21 Negative lead 22 Grooved part 23 Internal terminal board 24 Lower valve body 25 Insulating materials 26 Upper valve 27 Cap 28 Gasket
Claims
1. A positive electrode active material containing a lithium transition metal composite oxide containing 80 mol % or more of Ni relative to the total number of moles of metal elements excluding Li, and also containing Co and Mn, and in which Ti is present in the form of lithium titanate at least on the particle surface of the composite oxide, When particles having a volumetric particle size larger than a 70% particle size (D70) are defined as first particles, and particles having a volumetric particle size smaller than a 30% particle size (D30) are defined as second particles, a molar fraction (A2) of Ti with respect to a total mole number of metal elements excluding Li on the surface of the second particle is larger than a molar fraction (A1) of Ti with respect to a total mole number of metal elements excluding Li on the surface of the first particle, the molar fractions (A1) and (A2) of Ti being determined by X-ray photoelectron spectroscopy.
2. The positive electrode active material has the general formula Li a Ni b Co c Mn d Ti e O f 2. The positive electrode active material for a non-aqueous electrolyte secondary battery according to claim 1, having a composition represented by the formula: (wherein 0.8≦a≦1.2, b≧0.82, c≦0.12, 0.03≦d≦0.12, 0.01≦e≦0.05, and 1≦f≦2).
3. 3. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein a ratio (A2 / A1) of a molar fraction (A2) of Ti on the surface of the second particle to a molar fraction (A1) of Ti on the surface of the first particle is 1.20 or more.
4. 4. The positive electrode active material for a nonaqueous electrolyte secondary battery according to claim 1, wherein a molar fraction of Ti present on a particle surface relative to a molar fraction of Ti in the entire particle is larger for the second particles than for the first particles.
5. A positive electrode comprising the positive electrode active material according to any one of claims 1 to 4; A negative electrode; A non-aqueous electrolyte; A non-aqueous electrolyte secondary battery comprising:
Citation Information
Patent Citations
Positive electrode active material using surface-modified lithium nickel compound oxide, positive electrode material, lithium secondary battery, and manufacturing method for the surface-modified lithium nickel compound oxide
JP2004253305A
Positive active material and nonaqueous electrolyte secondary battery using it
JP2004319105A
Cathode for nonaqueous electrolyte secondary battery and its manufacturing method
JP2007265668A
Nonaqueous electrolyte secondary battery and method for manufacturing the same
JP2009224307A